Targeting acetyl-CoA carboxylase 1 for cancer therapy - Yu, Yong; Nie, Qingzhu; Wang, Ziyi; Di, Yu; Chen, Xiaolong; Ren, Kaiming (Frontiers in Pharmacology, 2023)
Metabolic adaptation is an emerging hallmark of tumors. De novo fatty acid synthesis is an important metabolic process to produce metabolic intermediates for energy storage, biosynthesis of membrane lipids and generation of signaling molecules. Acetyl-CoA carboxylase 1 (ACC1) is a critical enzyme in the fatty acid synthesis, which carboxylates acetyl-CoA carboxylic acid to form malonyl-CoA. The role of acetyl-CoA carboxylase 1 in fatty acid synthesis makes it a promising therapeutic target for various metabolic diseases such as non-alcoholic fatty liver disease, obesity and diabetes. Tumors have a high energy flow and a strong dependence on fatty acid synthesis. Thus, acetyl-CoA carboxylase inhibition has become a potential choice for anti-tumor therapy. In this review, we first introduced the structure and expression pattern of Acetyl-CoA carboxylase 1. We also discussed the molecular mechanisms of acetyl-CoA carboxylase 1 in the initiation and progression of various cancer types. Furthermore, acetyl-CoA carboxylase1 inhibitors has also been discussed. Collectively, we summarized the interplay between acetyl-CoA carboxylase 1 and tumorigenesis, indicating acetyl-CoA carboxylase 1 as a promising therapeutic target for tumor management.